Deal or no deal? Consensual arrangements as an instrument of European competition policy - Oliver Budzinski; Björn A. Kuchinke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
Roughly during the last decade, European Competition Policy has undergone a series of fundamental changes. All four areas - cartel policy, merger policy, abuse control, and state aid control - have been subject to a modernization process, which led to a focus on analysing the effects of individual cases and established a tendency towards deciding each case on its individual merits. These changes can be understood as a move away from rule-based competition policy towards a case-by-case approach. The case-by-case approach especially includes consensual arrangements, so-called 'deals' between the competition authority and business companies. Therefore, this paper will discuss the pros and cons of 'deals' as an instrument of (European) competition policy. The paper's central focus lies on the economic analysis of the advantages and disadvantages of using consensual arrangements as a relevant instrument of European competition policy. With respect to European competition policy, we conclude that we need to issue a note of caution. From an economic perspective, an expansion of consensual elements necessarily walks hand in hand with a continual weakening of the protection of competition. Consumer welfare will not benefit from expanding the role and importance of consensual arrangements as a means of European competition policy.
Keywords: L40; K21; D02; P16; 330; European competition policy; consensual arrangements; antitrust settlements; merger control; deals; political economics